Stressors among students' in higher education instituion in Malaysia / Siti Rapidah Omar Ali, Nur Shafini Mohd Said & Khalid Amin Mat - Omar Ali, Siti Rapidah; Mohd Said, Nur Shafini; Mat, Khalid Amin (2020)
Considerable stress can lead to range of issues that adversely influence a student's well-being. Mental illness among youth is apparently a major problem worldwide nowadays. This study tried to examine the relationship between stressors and individual well-being among undergraduate students. A sample of 350 selfadministered questionnaire were distributed to undergraduate students in a public university in East Coast of Peninsular Malaysia. The study adopted simple random sampling method. Pearson correlation has been used to analyze the relationship between independent variables and dependent variable. Finding shows that all stressors elements have positive relationship with the psychological well-being with very low correlation. Only social support stress indicates moderate, positive correlation with the psychological well-being. Multiple regression analysis displays, only social support stress significantly influence psychological well-being while other three variables have been found not significantly influence psychological well-being. Hence, only hypothesis three was accepted while others was rejected.